Combustion and emission characteristics of an Acetone-Butanol-Ethanol (ABE) spark ignition engine with hydrogen direct injection. (23rd August 2021) - Li, Decheng; Wang, Haoyu; Yu, Xiumin; Yang, Hang
Abstract: Butanol could reduce emissions and alleviate the energy crisis as a bio-fuel used on engines, but the production cost problem limits the application of butanol. During the butanol production, ABE (Acetone-Butanol-Ethanol) is a critical intermediate product. Many studies researched the direct application of ABE on engines instead of butanol to solve the production cost problem of butanol. ABE has the defects of large ignition energy and vaporization heat. Hydrogen is a gaseous fuel with small ignition energy and high flame temperature. In this research, ABE port injection combines with hydrogen direct injection, forming a stratified state of the hydrogen-rich mixture around the spark plug. The engine speed is 1500 rpm, and λ is 1. Five αH2 (hydrogen blending fractions: 0, 5%, 10%, 15%, 20%) and five spark timings (5°, 10°, 15°, 20°, 25° CA BTDC) are studied to observe the effects of them on combustion and emissions of the test engine. The results show that hydrogen addition increases the maximum cylinder pressure and maximum heat release rate, increases the maximum cylinder temperature and IMEP, but the exhaust temperature decreases. The flame development period and flame propagation period shorten after adding hydrogen. Hydrogen addition improves HC and CO emissions but increases NOx emissions. Particle emissions decrease distinctly after hydrogen addition. Hydrogen changes the combustion properties of ABE and improves the test engine's power and emissions. The combustion in the cylinder becomes better with the increase of αH2, but a further increase in αH2 beyond 5% brings minor improvements on combustion. Highlights: A technical conception of hydrogen/ABE combined injection is put forward. Hydrogen addition optimizes the combustion of ABE and improves IMEP. The HC and CO emissions decrease with αH2 increasing. Particle number emissions improved after hydrogen addition. The ABE mixture is more sensitive to hydrogen addition than αH2 .